Analysis of the role of the type III effector inventory of Pseudomonas syringae pv. phaseolicola 1448a in interaction with the plant. - Zumaquero, Adela; Macho, Alberto P; Rufián Plaza, José Sebastián; Beuzón-López, Carmen del Rosario (American Society for Microbiology, 2010)
In Pseudomonas syringae, the type III secretion system (T3SS) is essential for disease in compatible hosts and for eliciting the hypersensitive response in incompatible hosts. P. syringae pathovars secrete a variable number of type III effectors that form their secretomes. The secretome of Pseudomonas syringae pv. phaseolicola 1448a (Pph1448a) currently includes 22 experimentally validated effectors, one HrpL-regulated candidate for which translocation results have been inconsistent, two translocated candidates for which in planta expression has not been established, one bioinformatically identified candidate, and six candidates that have been experimentally discarded. We analyzed the translocation and/or expression of these and other candidates to complete the Pph1448a effector inventory, bringing this inventory to 27 bona fide effectors, including a new one that does not belong to any of the previously described effector families. We developed a simple process for rapidly making single and double knockout mutants and apply it to the generation of an effector mutant collection that includes single knockouts for the majority of the Pph1448a effector inventory. We also generated two double mutant strains containing effectors with potentially redundant functions and analyzed the virulence of the single and double mutant strains as well as strains expressing each of the effectors from a plasmid. We demonstrate that AvrB4-1 and AvrB4-2, as well as HopW1-1 and HopW1-2, are fully redundant and contribute to virulence in bean plants, thus validating this approach for dissecting the contribution of the Pph1448a type III effector inventory to virulence.
https://v2.sherpa.ac.uk/id/publication/6219
Keywords: Relaciones planta-microbio; Plantas - Microbiología; Pseudomonas syringae; Type III Secretion System